Effects of scaffolding in aiding student’s understanding of a text / Sandra Sim Phek Lin - Sim, Sandra (Universiti Teknologi MARA Kampus Samarahan, 1999)
Understanding a text is no doubt stressed by teachers or instructors in every school and institution of higher learning. However, in order to yield positive results, scaffolds need to be provided by teachers to help guide their students to a better understanding of a text. The term ‘scaffold’ refers to visible and audible support which is both adjustable and temporary given by a teacher to a learner to help him initially so that later he can function in his ‘zone of proximal development’ (operate independently). This case study aims to find out how scaffolds provided by the teacher help a student to understand a text. This study indicates positive effects of the use of scaffolds in assisting student's comprehension of a text.